Current issues in external and internal auditing - Vinten, Gerald (Managerial auditing journal ; v, 2004)
Internal audit education is now concentrated in just a few tuition providers within the UK, a decrease from the 1980s. Generally it is not represented at all in its own right within higher education, and may just receive a passing reference as contrasted with external auditing. Hence it is scarcely perceptible and submerged. Even where it is rarely present it seems to have become "secularised", its influence waning under the banner of "general management". The professional body, the Institute of Internal Auditors - UK and Ireland, is too busy selling its highly profitable distance learning cou.